Severe alterations caused by the indigenous pyralid Denticera divisella (Dup.) on the cultivated Euphorbia x lomi Rauh (Euphorbiaceae) in Sicily, with notes on some agronomic aspects (Lepidoptera: Pyralidae) - Bella, Salvatore; Spina, Alfio; Salamone, Adele; Fascella, Giancarlo (Fragmenta entomologica, 2017)
In this contribution, we report information on the severe alterations caused by the stem boring moth Denticera divisella (Duponchel, 1842) (Lepidoptera, Pyralidae) on the cultivated Euphorbia x lomi Rauh (Euphorbiaceae). This plant is an ornamental hybrid of recent origin, much appreciated for the attractive inflorescences, used both as an apartment plant and, especially in Sicily, as an outdoor plant. In this region, this species is an important source of income for many nursing businesses that have replaced it with some species whose market was in crisis. The pyralid is an indigenous species with an European distribution, while Euphorbia x lomi is a hybrid from Thailandia native to Madagascar, with many varieties currently cultivated in the world. The observations were conducted in Sicily in 2014 and 2015.